Comparative study of Vitamin D levels in diabetic and non- diabetic women and its correlation with age and seasonal variation - Abdulhadi Mohamed Jumaa (Tikrit Journal of Pure Science)
Background  vitamin D has characteristics features of a hormone, and accordingly vitamin D is a pro-hormone, rather than a true vitamin. Active form of vitamin D is binding to vitamin D receptors (VDR) then started its main action inside the  body.